The Impact of Assets Structure, Liquidity, Business Risk and Company Size on Capital Structure - Mustofa, Nur Huri; Lestari, Sylvia indah (El-Barka, 2021)
Expenditure decisions and demand are closely related to the arrangement of capital structure. The purpose of this research is to determine the impact of asset structure, liquidity, business risk and company size on the capital structure of ISSI listed companies during 2017-2020. The method of data collection for this research is to collect annual financial reports on the IDX website. The purposive sampling method utilized to analyze sample of 35 companies obtained. The analytical techniques used are stationarity test, statistics passing T test, F test, coefficient of determination (R2), classical assumption test, and multiple linear regression test. Data management is used with Eviews 12 tools. The research results prove that the Asset Structure has a positive and significant impact on the capital structure. Liquidity has a positive and significant impact on capital structure. Business risk has a positive and insignificant effect on capital structure. Company size has a positive impact on capital structure and is not significant.